PENGARUH IKLAN DIGITAL & KONTEN PROMOSI TERHADAP MINAT BELI MELALUI CITRA MEREK SEBAGAI INTERVENING VARIABLE PADA USAHA VEGAN LAND - Cendrawan, Maitreyawira Aryanathan; Utami, Christina Whidya (JURNAL ILMIAH EDUNOMIKA, 2025)
The aim of this thesis research is to analyze the impact of digital advertising and promotional content on purchase intention through brand image as an intervening variable in Vegan Land's business. The research method used is quantitative, employing non-probability sampling with purposive sampling involving 100 respondents. The results indicate that digital advertising does not have a significant effect on purchase intention, while promotional content has a significant influence on purchase intention. Brand image has a significant impact on purchase intention, and digital advertising significantly affects brand image. However, promotional content does not significantly affect brand image. Digital advertising has a significant impact on purchase intention when brand image serves as the intervening variable, whereas promotional content does not have a significant effect on purchase intention when brand image is the intervening variable